1997
DOI: 10.1093/emboj/16.3.659
|View full text |Cite
|
Sign up to set email alerts
|

A small heat shock protein stably binds heat-denatured model substrates and can maintain a substrate in a folding-competent state

Abstract: The small heat shock proteins (sHSPs) recently have been reported to have molecular chaperone activity in vitro; however, the mechanism of this activity is poorly defined. We found that HSP18.1, a dodecameric sHSP from pea, prevented the aggregation of malate dehydrogenase (MDH) and glyceraldehyde-3-phosphate dehydrogenase heated to 45 degrees C. Under conditions in which HSP18.1 prevented aggregation of substrates, size-exclusion chromatography and electron microscopy revealed that denatured substrates coated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

35
676
0
17

Year Published

1998
1998
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 725 publications
(728 citation statements)
references
References 43 publications
35
676
0
17
Order By: Relevance
“…In vitro , the addition of the HSP70/HSP40 refolding machinery is required for the refolding reaction (Lee et al ., 1997). This has been reproduced in living cells using luciferase as a substrate (Nollen et al ., 2001; Bryantsev et al ., 2007).…”
Section: Resultsmentioning
confidence: 99%
“…In vitro , the addition of the HSP70/HSP40 refolding machinery is required for the refolding reaction (Lee et al ., 1997). This has been reproduced in living cells using luciferase as a substrate (Nollen et al ., 2001; Bryantsev et al ., 2007).…”
Section: Resultsmentioning
confidence: 99%
“…the observation that the size of HSP27 oligomers transiently increases in HeLa and L929 cells treated with TNF-a which induces rapid phosphorylation of the protein (Mehlen et al, 1995b(Mehlen et al, ,c, 1997. However, these observations were di cult to interprete as di erent populations of sHSP could exist in these cell lines and the methods used to detect larger oligomers could also identify small oligomers associated with unfolded proteins (Ehrnsperger et al, 1997;Lee et al, 1997). Our conclusion is based on the observation that the aspartate mutant of HSP27 forms large oligomers in REG cells cultured at con¯uence or forming tumors when injected subcutaneously in rodents.…”
Section: Discussionmentioning
confidence: 99%
“…Eukaryotic smHSP are considered to be molecular chaperones (Arrigo and Landry, 1994). Chaperone activity for plant smHSP was demonstrated in vitro (for example Lee et al, 1997) and suggested in vivo (reviewed by Waters et al, 1996). Great differences exist, however, between mammalian and plant smHSP with respect to the number of expressed proteins and their localization, and their ability to be regulated by phosphorylation.…”
Section: Introductionmentioning
confidence: 99%